This is the Bernoully equation
"y=uv,y'=u'v+uv'," then "v(u'+\\frac{x}{1-x^2}u)+(uv'-xu^\\frac{1}{2}v^\\frac{1}{2})=0"
"\\int \\frac{du}{u}=-\\int \\frac{x}{1-x^2}dx" hence "u=(1-x^2)^\\frac{1}{2}," then
"(1-x^2)^\\frac{1}{2}v'-x(1-x^2)^\\frac{1}{4}v^\\frac{1}{2}=0" hence "\\int \\frac{dv}{v^\\frac{1}{2}}=\\int \\frac{x}{(1-x^2)^\\frac{1}{4}}dx" hence
"v=(-\\frac{(1-x^2)^\\frac{3}{4}}{3}+C)^2" then "y=(1-x^2)^\\frac{1}{2}v"
as "y(0)=1" hence "C=4\/3" then "y(x)=\\frac{1}{9}(1-x^2)^\\frac{1}{2}(4-(1-x^2)^\\frac{3}{4})^2"
Comments
Leave a comment